Canadian Optometric Low Vision: Predictive Factors and Regional Comparisons - Lam, Norris; Leat, Susan J (Canadian Journal of Optometry, 2016)
Purpose: To investigate the regional differences in low vision (LV) provision across Canada and to identify predictive factors for the provision of more extensive low vision services (LVS). Methods: Practising optometrists across Canada were invited to participate in a questionnaire that investigated personal and practice demographics, levels of LVS offered, patterns of referrals and barriers to provision of LVS. Results: 459 optometrists responded. Predictive factors for providing more extensive LVS included: optometrists with >15 years of practice, having a local LV optometrist/ophthalmologist within one day’s travel, not having a multi-disciplinary LV clinic within one-day’s travel, working in a practice in a population of <50,000, and having 2+ optometrists in the same practice. Regional differences were found in the following variables: the presence of an optometrist offering LVS within the respondent’s primary practice, referral criteria, the type of LV provider receiving the referral, and the perceived quality of LVS. Conclusions: LVS are provided differently across Canada and the availability of government-funded LVS appeared to enhance optometric referrals to multidisciplinary low vision clinics. Optometrists who were in a group practice setting, who had practiced for >15 years and who worked in a less populated area were more likely to provide more extensive LVS.